The Violin - Riggs, Robert, 1946- (Book collections on Project MUSE., 2016)
With a colourful history that spans 450 years, the violin has proven to be one of the world?s most important and versatile instruments. Addressed to performing musicians, serious concertgoers, and collectors of0recordings, The Violin offers insightful, up-to-date essays on a wide range of topics. Essays discuss beloved masterpieces from the violin?s solo repertoire, with individual chapters on the Italian Baroque, Bach, Mozart, 0Beethoven, and the violin concerto in the nineteenth and twentieth centuries, as well as the evolution of0performance styles and interpretation as documented in recordings. The volume also illustrates the broad0cultural and geographic reach of the instrument, offering readers a taste of the traditional music of Argentina, Mexico, Norway, and India, in which the violin?s participation is an essential and characteristic element. Other 0chapters are devoted to American fiddling and to the violin and violinists as metaphors in literature and the visual arts.